Awqaf-led green finance: a technical know-how - Mohd Zain, Nor Razinah; Tounchibine, Oumaima; Mohd Noor, Azman; Lechheb, Houda (Routledge, Taylor & Francis Group, 2025)
Looking towards 2030, it is evident that significant endeavours are being commenced through strategic initiatives to effectively realise the UN Sustainable Development Goals (SDGs). Numerous significant stakeholders such as government agencies, public and private sectors, and authoritative regulators or policymakers are actively engaging in ensuring a harmonious integration of the SDGs' three primary components, namely environment, social, and economy. While facing the multifaceted matters of SDGs, the advent of green finance has emerged as an essential mechanism to direct attention towards safeguarding and conserving the environment, without neglecting social and economic components. With such a backdrop, Awqaf undeniably has an integral role to play in the application of green finance in the modern world. Consistent with its classical practices, modern practices of Awqaf are suitable to meet the stipulated objective of green finance. By applying qualitative and meta-analysis approaches, the researchers evaluate the practices of Awqaf as part of the green finance mechanism. Whilst adoptions of Awqaf led-green finance vary from one country to another, it is apparent that as long as it fulfils the Shari'ah-compliance nature, Awqaf can be utilised as a successful tool for green finance-based projects. Indonesia seems to be the giant in leading the way for Awqaf led-green finance at the global scale, and is followed closely by Malaysia and Turkey.